Association between television viewing and early childhood overweight and obesity: a pair-matched case-control study in China - Jiajin Hu; Ning Ding; Liu Yang; Yanan Ma; Ming Gao; Deliang Wen (BMC, 2019)
Abstract Background Television (TV) viewing may affect children's obesity status. In the present study the association between TV viewing and early childhood overweight/obese status was investigated as well as the association based on age difference. Methods The present study included 933 children 1-5 years of age that were individually matched on a 1:2 (cases: controls) ratio based on age and community. Cochran-Mantel-Haenszel test was used to evaluate the association between TV viewing time and the related unhealthy behaviors. Conditional logistic regression models were used to quantify the association between TV viewing and children overweight/obese status in two age groups. The effects of TV viewing-related behaviors on the associations were further investigated. Results TV viewing time > 1 h was positively associated with the prevalence of TV viewing-related unhealthy behaviors (P < 0.05). After controlling for these behaviors, the association between TV viewing and childhood overweight/obese status was significant among 4- to 5-year-old children (odds ratio, OR = 1.72, 95% confidence interval, CI: 1.16--2.54), but not significant among 1- to 3-year-old children. Conclusions Childhood overweight/obese status was positively associated with longer TV viewing time only among 4- to 5-year-old children. The results from the present study may help in identifying the population susceptible for overweight and obesity caused by TV viewing.